ANALISIS SWOT DALAM MENGETAHUI STRATEGI BERSAING (Kasus Hotel Pangeran Pekanbaru) - Hayatul Mardiyah; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Hotel Pangeran Pekanbaru is one of the four star hotel in Pekanbaru. Hotel is a type of business that is engaged in services which compete to provide good facilities and services. Increase the number of hotels in Pekanbaru, the Hotel Pangeran Pekanbaru should be able to compete and survive in this competitive hospitality industry. This study aims to identify and analyze the competitive strategy Hotel Pangeran Pekanbaru. This is a descriptive study with case study and data collection techniques performed by interviewing the parties involved in this study. From the results of interviews conducted can be analyzed that the Hotel Pangeran Pekanbaru continue competition in improving the quality of service and facilities that will be offered to consumers by putting prices, products, services corresponding to the four-star standard and continue to compete with a new kind of hotel in Pekanbaru.Keywords: business strategy, SWOT (Strengths, Weakness, Opportunity, Treats), SWOT Analysis